2016
DOI: 10.1038/nmeth.4108
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly evolving homing CRISPR barcodes

Abstract: We present here an approach for engineering evolving DNA barcodes in living cells. The methodology entails using a homing guide RNA (hgRNA) scaffold that directs the Cas9-hgRNA complex to target the DNA locus of the hgRNA itself. We show that this homing CRISPR-Cas9 system acts as an expressed genetic barcode that diversifies its sequence and that the rate of diversification can be controlled in cultured cells. We further evaluate these barcodes in cell populations and show the barcode RNAs can be assayed as s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
209
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(211 citation statements)
references
References 33 publications
1
209
0
1
Order By: Relevance
“…Recently, high-throughput lineage-tracing methods have been developed using CRSIPR/Cas9-based multiplexing DNA barcodes synthesis [5458]. These barcodes are stably registered in the genome and inherited during cell division and differentiation.…”
Section: Future Directionsmentioning
confidence: 99%
“…Recently, high-throughput lineage-tracing methods have been developed using CRSIPR/Cas9-based multiplexing DNA barcodes synthesis [5458]. These barcodes are stably registered in the genome and inherited during cell division and differentiation.…”
Section: Future Directionsmentioning
confidence: 99%
“…By triggering expression of mSCRIBE in response to NF-κB activation, the researchers were able to record the duration of tumor necrosis factor alpha (TNF-α) exposure in vitro and lipopolysaccharide-induced inflammation in vivo [43••]. Utilizing a similar strategy, Kalhor et al traced cell lineages by barcoding cells with arrays of self-targeting sgRNAs that evolve into unique signatures that record the cumulative mutational history from prior cell generations [44]. More generally, greater understanding of programmed cellular responses to environmental cues is essential for engineering systems that interface robustly with physiological stimuli.…”
Section: Sensing Recording and Reprogramming Cellular Functionsmentioning
confidence: 99%
“…This improvement could be implemented because these barcodes can be repeatedly targeted [25]. Additionally, Kalhor et al showed that this technique can be coupled with fluorescence in situ sequencing (FISSEQ) to preserve spatial information while achieving barcode readout.…”
Section: Self-targeting Crispr Barcodesmentioning
confidence: 99%
“…In addition, CRISPR-Cas-based recorders now enable vast numbers of barcodes to be generated over time in order to record cell lineage and important biological events. Based on the studies by Kalhor et al that quantify the information that a single CRISPR site can encode, CRISPR-based recorders can produce ~(2 5 ) n unique barcodes, where n is equal to the number of arrayed target sites [25]. Arraying ten sites together yields more than enough barcodes to label every cell in the human body (~3.7×10 13 ) [26].…”
Section: Summary and Perspectivementioning
confidence: 99%